EMIC Wave Events During the Four GEM QARBM Challenge Intervals. Issue 8 (16th August 2018) - Engebretson, M. J.; Posch, J. L.; Braun, D. J.; Li, W.; Ma, Q.; Kellerman, A. C.; Huang, C.‐L.; Kanekal, S. G.; Kletzing, C. A.; Wygant, J. R.; Spence, H. E.; Baker, D. N.; et al.
Abstract: This paper presents observations of electromagnetic ion cyclotron (EMIC) waves from multiple data sources during the four Geospace Environment Modeling challenge events in 2013 selected by the Geospace Environment Modeling Quantitative Assessment of Radiation Belt Modeling focus group: 17 and 18 March (stormtime enhancement), 31 May to 2 June (stormtime dropout), 19 and 20 September (nonstorm enhancement), and 23–25 September (nonstorm dropout). Observations include EMIC wave data from the Van Allen Probes, Geostationary Operational Environmental Satellite, and Time History of Events and Macroscale Interactions during Substorms spacecraft in the near‐equatorial magnetosphere and from several arrays of ground‐based search coil magnetometers worldwide, as well as localized ring current proton precipitation data from low‐altitude Polar Operational Environmental Satellite spacecraft. Each of these data sets provides only limited spatial coverage, but their combination shows consistent occurrence patterns and reveals some events that would not be identified as significant using near‐equatorial spacecraft alone. Relativistic and ultrarelativistic electron flux observations, phase space density data, and pitch angle distributions based on data from the Relativistic Electron‐Proton Telescope and Magnetic Electron Ion Spectrometer instruments on the Van Allen Probes during these events show two cases during which EMIC waves are likely to have played an important role in causing major flux dropouts of ultrarelativistic electrons, particularly near L * ~4.0. In three other cases, identifiable smaller and more short‐lived dropouts appeared, and in five other cases, these waves evidently had little or no effect. Key Points: EMIC waves can rapidly deplete fluxes of ultrarelativistic electrons, but their occurrences are limited in both space and time EMIC wave observations by magnetospheric spacecraft are supplemented by observations from ground‐based magnetometers and POES satellites Many but not all EMIC wave events correlated with major or minor depletions of ultrarelativistic electrons observed by the Van Allen Probes